Pelatihan Berpikir Positif Terhadap Konsep Diri Remaja yang Tinggal Di Panti Asuhan - Dhea Ravea Eka Putri (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2017)
Self-concept  is  an  individual  view  about  their  self  based  on  a  variety  of experiences during their life. This topic is interesting to be examined in orphanage context, because adolescents have various experiences in their life before and during their stay in the orphanage. Aim of this study was to understand the role of positive thinking training onadolescents’ self-concept who lived in an orphanage. This research was quasi-experimenta lwith nonrandomized pre-test post-test control group design model. Measuring instruments used self-concept scale. Subjects of this study were 30 adolescents who live in Al-Hidayah Batu orphanage, and were in the age range 13-17 years and have low and medium selfconceptscore category. Subject selection technique used purposive sampling. However, for subject’s classification on experimental and control group used random sampling method. Analysis used Independent Sample t-Test, and p= 0,003 (p<0,05). The conclusion was positive thinking training could improve self concept of adolescents who lived in orphanages.Keywords: positive thingking training, self concept, orphanage, adol